Jigsaw Type Cooperative Learning Assisted by Genially Media to Improve the Students Activity and Learning Outcomes of IPAS - Chairul Kusuma Anjani; Ana Fitrotun Nisa; Akbar Al Masjid; Banun Havifah Cahyo Khosiyono (Postgraduate, University of Mataram, 2025)
This study aims to analyze the effectiveness of the implementation of the Jigsaw type cooperative learning model assisted by Genially media in improving the activity and learning outcomes of fifth grade students of Triharjo Elementary School in the subject of science. This study uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart model which is carried out in two cycles at Triharjo Elementary School, Sleman, to improve the activity and learning outcomes of fifth grade students in the subject of science. Data were collected through observations of student learning activities using observation sheets and multiple-choice tests of 20 questions that have been validated by material experts. The success of this study was determined based on an increase in student activity that reached a minimum of 75% and student learning outcomes that met the achievement criteria of 80% with a minimum score of 75. This study shows that the implementation of the Jigsaw type cooperative learning model assisted by Genially media is effective in improving the activity and learning outcomes of fifth grade students of Triharjo Elementary School in the subject of science. Before the action, student participation and learning outcomes were still low, but after the implementation of this model, there was a significant increase, especially in Cycle II with an average learning outcome reaching 77.71%. This learning model has been proven to increase student motivation, engagement, and understanding, making it a more effective alternative learning method.